Investigation on cage motions in high speed angular contact ball bearing with clearance fit between the outer ring and housing. (March 2023) - Yan, Shuping; Qu, Qiong; Liu, Minghui; Zhang, Yubing; Yu, Chunlan; Wang, Fengtao
As one of the bearing vibration sources, cage motions were often investigated for distinguishing the bearing performance. However, when the ball bearing works under complex conditions, there may be clearance fit between outer ring and housing, cage motions are affected seriously, which is less considered in previous studies. Thus, a dynamic model for the ball bearing with clearance fit was proposed, and effects of clearance fit on the cage motions were studied. The constructed model is verified by the experiment in the literature. In the obtained results, the whirl orbit, poincare map, cage velocity deviation ratio were given for defining the whirl stability of cage motions. The cage whirl stability declined with the enlargement of clearance fit and initial contact angle. Whereas, the cage whirl stability enhanced with the increasing guiding clearance. The above results may offer some advice for the design and using of angular contact ball bearing.